PENGARUH DPK, IMBAL HASIL SBIS, PUAS, DAN TINGKAT INFLASI TERHADAP PEMBIAYAAN BANK SYARIAH DI INDONESIA - Rusida Delfa Kendi Hawa; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
The purpose of this study is to analyze the factors that affect the sharia banking in channeling funds in the period January 2012 to December 2016, both partially and simultaneously. The data used are secondary data, with four independent variables namely DPK, SBIS Return, PUAS, and Inflation Rate which were obtained from official website of Bank Indonesia and OJK, as well as financing data of shariah bank as dependent variable obtained from the official web of Bank Indonesia. The research method used is descriptive quantitative method by using multiple linier regression analysis technique. The result of the research shows that the four factors in this study, namely DPK, SBIS Return, PUAS, and Inflation Rate, partially as well as simultaneously have a positive and significant effect on the channeling of Islamic bank funds.    REFERENCESAscarya, 2012. Buletin Ekonomi dan Perbankan: Alur Transmisi Kebijakan Moneter Ganda di Indonesia. Jurnal Ekonomi Islam RepublikaAnshori, Muslich dan Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Arifin Z. 2009. Dasar-dasar Manajemen Bank Syariah. Jakarta(ID): Azkia Publisher.Dahlan, Rahmad. 2014. Pengaruh Tingkat Bonus Sertifikan Bank Indonesia Syariah dan Tingkat Inflasi Terhadap Pembiayaan Bank Syariah Di Indonesia. Jurnal Etikonomi Vol. 13 No. 2.Danang, Sunyoto. 2007. Metodologi Penelitian Ekonomi, Cetakan Pertama. CAPS. Yogyakarta.Dendawijaya, Lukman. 2009. Manajemen Perbankan. Jakarta: Pernebit Ghalia IndonesiaGhozali, I. (2011). Aplikasi Analisis Multivariate dengan Program IBM SPSS 19. Semarang: Universitas Diponegoro.Karim, Adiwarman A. 2007. Ekonomi Makro Islam. Jakarta: PT Raja Grafindo Persada.Karnaen, Perwaatmadja dan M.Syafi’I Antonio. 1997. Apa dan Bagaimana Bank Islam. Yogyakarta: Dana Bhankti Wakaf.Kuncoro, Mudrajat. 2003. Metode Riset untuk Bisnis & Ekonomi, Bagaimana Meneliti & Menulis Tesis. Erlangga, Jakarta.Peraturan Bank Indonesia No.6/7/PBI/2004 tentang SWBIPeraturan Bank Indonesia No. 10/18/PBI/2010 tentang SBISPeraturan Bank Indonesia No. 12/19/PBI/2010 tentang Dana Pihak KetigaPutong, Iskandar. 2003. Pengantar Ekonomi Mikro dan Makro. Ghalia IndonesiaUndang-undang Republik Indonesia Nomor Nomor 7 Tahun 1992 tentang PerbankanUndang-undang Republik Indonesia Nomor Nomor 10 Tahun 1999 tentang PerbankanSamuelson, Paul. A and Willam D. Nordhaus. 1995. Economics Fifteen Edition. New Baskerville: York Graphic Services, Inc.Santoso, Singgih. 2000. Latihan SPSS Statistik Parametrik. Jakarta: PT Elex Media Komputindo.Sudarsono, Heri. 2005. Bank dan Lembaga Keuangan Syariah. Yogyakarta EKONISIA.Sujarweni, V. Wiratna. 2014. SPSS Untuk Penelitian. Yogyakarta: Pustaka Baru PressSukirno, Sadono, Makroekonomi: Teori Pengantar, Jakarta: Raja Grafindo Persada, 2004.Tri Basuki, Agus. 2016. Analisis Regresi dalam Penelitian Ekonomi dan Bisnis, Jakarta: Rajawali Pers.Widyatsari, Any. 2014. Pasar Uang Antar Bank Syariah. Economic: Jurnal Ekonomi dan Hukum Islam.